2017
DOI: 10.2196/ijmr.7352
|View full text |Cite
|
Sign up to set email alerts
|

Shaping an Effective Health Information Website on Rare Diseases Using a Group Decision-Making Tool: Inclusion of the Perspectives of Patients, Their Family Members, and Physicians

Abstract: BackgroundDespite diverging definitions on rare conditions, people suffering from rare diseases share similar difficulties. A lack of experience by health professionals, a long wait from first symptoms to diagnosis, scarce medical and scientific knowledge, and unsatisfactory treatment options all trigger the search for health information by patients, family members, and physicians. Examining and systematically integrating stakeholder needs can help design information platforms that effectively support this sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Finding accurate information on the Internet is especially problematic for rare diseases, as approximately 50% of these disorders do not have a foundation providing specific patient information. 1 Despite studies showing frequent use of the Internet by parents of children with rare conditions [27][28][29][30][31][32], one study reviewing 693 websites about rare diseases found that in general the quality of information provided was poor [33]. Our results only describe outcomes that may occur when patients are provided with accurate information, personal contact, and a path to achieving diagnosis.…”
Section: Limitationsmentioning
confidence: 69%
“…Finding accurate information on the Internet is especially problematic for rare diseases, as approximately 50% of these disorders do not have a foundation providing specific patient information. 1 Despite studies showing frequent use of the Internet by parents of children with rare conditions [27][28][29][30][31][32], one study reviewing 693 websites about rare diseases found that in general the quality of information provided was poor [33]. Our results only describe outcomes that may occur when patients are provided with accurate information, personal contact, and a path to achieving diagnosis.…”
Section: Limitationsmentioning
confidence: 69%
“…In the rare disease arena, PACs often become experts in their particular disease out of necessity [15,17,19]. Being patients themselves or in the front lines of patient care, they experience heavy disease, emotional, and financial burdens due to the gravity of the disease and the complexity of the associated care [15].…”
Section: Discussionmentioning
confidence: 99%
“…Primary care physicians (PCPs) are typically trained for and are familiar with approximately 400 different diseases that present most often in their environment [15]. Since PCPs are usually the first to be consulted by patients and caregivers, they need to be able to recognize the early symptoms of rare, often progressive, diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare diseases are typically severe, mostly genetic in origin, and the majority of cases are reported in patients with very early onset (Luzzatto et al, ). Therefore, efforts have been made continuously to identify the causative mutations for these infantile‐onset rare Mendelian diseases (Bacchelli & Williams, ), which is of great importance for patient management (Silibello et al, ) and family counseling (Babac, ).…”
Section: Introductionmentioning
confidence: 99%